A study of demographic variables affecting tubectomy in a tertiary care centre in India - Amrita Chaurasia; Nidhi Sachan; Shalini Singh; Saumya Saxena (International Journal of Medical Research and Review, 2018)
Introduction: Family planning is one of the fundamental pillars of safe motherhood and a reproductive right. The practice of family planning is influenced by socio demographic factors.Material and Methods: All patients undergoing tubectomy were evaluated for age, parity, religion, belonging to rural/urban areas and whether undergoing tubectomy with/without MTP. Ethical clearance for the study was taken from the Institutional ethics committee. The statistical significances of differences in different variables were evaluated by calculating p-values.Results: Study demonstrated that majority of tubectomy acceptors (86.9%) belonged to age group of 25-30 years. Maximum no of couples (44.5%) had 3 children before opting tubectomy, next predominant group was of couple who had 1-2 children (31.2%). 96.8% of couples were Hindu and only 3.1% from Muslim community. 73.6% of the total tubectomy acceptors studied, were from rural areas, and 26.3% were from urban regions. 29% of couple had medical termination of pregnancy before sterilization.Conclusion: More of the young population in India are opting for tubectomy. Still women with 3 children are predominating the tubectomy group. Religion has a huge impact on contraceptive practices in India. Removal of the religious taboos is essential for proper implementation of family planning programmes. Maximum of the rural people are enrolling for tubectomy. There is need to spread the usage of spacing methods amongst this group. A significant no of people opted for tubectomy only when they became pregnant with the unwanted child, hence went for sterilization after medical termination of pregnancy.